Analysis of Iconic Grammatical Elements of the Sesulih Pratama Purusa Phrase in the Text of Raden Said Published by Perpusnas Press - R. Adi Deswijaya; Agus Efendi; Tri Widiatmi; Nur Auliyani, Zalfa Zahiroh; Alfi Sahri (Sutasoma : Jurnal Sastra Jawa, 2025)
This research aims to (1) analyze the grammatical elements of sesulih pratama purusa phrases or third-person pronominal phrases found in the transliterated book of Raden Said text. (2) explain the types of iconicity of sesulih pratama purusa phrases or third-person pronomina phrases found in the transliterated book of Raden Said text; and (3) describe the reference form and meaning of the iconicity of sesulih pratama purusa phrases or third-person pronomina phrases found in the transliterated book of Raden Said text. Data collection was conducted using the listening method with a note-taking technique. The data were analyzed using agih method with semantic approach. This study found that the grammatical elements of third-person pronomina phrases and nomina phrases hold the most usage role, as many as 20 times from the total data of 28 third-person pronomina phrases. A total of 28 forms of third-person pronominal phrases were found to be the most iconic in the form of symbols. The most common reference for third-person pronoun phrases is endophoric reference, anaphora, followed by katafora.